Tinjauan Pemenfaatan Data Sensus Harian Rawat Inap di Rumah Sakit Santa Elisabeth Medan - Bernad Julvian Zebua; Irma Novitasari Br. Sihotang (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Hospitals are very complex, dynamic, capital-intensive, and labor-intensive institutions that are multi-disciplinary and are influenced by an ever-changing environment (Permenkes No. 340 of 2010). Medical Record is a file containing notes and documents about patient identity, examination, treatment, actions and other services that have been provided to patients (Permenkes No. 269/MENKES/PER/III/2008). The daily inpatient census is a collection of patient data entering and leaving the ward. The daily inpatient census contains information on all incoming, transferred, transferred, and discharged patients both alive and dead for 24 hours. Therefore, the researcher wanted to review the implementation of the daily inpatient census at Elisabeth Hospital Medan related to the implementation of the census in accordance with the Standard Operating Procedures (SPO), the daily census flow, the timeliness of the implementation, the comparison of manual census data and the obstacles in carrying out the daily inpatient census. The method used in this research is interview and active participation observation. Based on the above results regarding the manual census and SHAPIRA in St. Ignatius Elisabeth Hospital Medan, Shapira's census, the number of patients always exceeds the bed capacity, even three times the available bed capacity.